2020
DOI: 10.3389/fendo.2020.00602
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers to Post-partum Diabetes Screening Among Mothers With a History of Gestational Diabetes Mellitus–A Qualitative Study From Singapore

Abstract: Introduction: Gestational Diabetes Mellitus (GDM) affects one in six births worldwide. Mothers with GDM have an increased risk of developing post-partum Type-2 Diabetes Mellitus (T2DM). However, their uptake of post-partum diabetes screening is suboptimal, including those in Singapore. Literature reports that the patient-doctor relationship, mothers' concerns about diabetes, and family-related practicalities are key factors influencing the uptake of such screening. However, we postulate additional f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 26 publications
1
36
2
Order By: Relevance
“…The results of this study also showed for mothers undergoing operative delivery in patients with lumbar anesthesia that there are communications between patients and doctors in the surgery process. Communication is what makes mothers have life experience so that delivery by way of operative delivery is not scary, but it is a labor that can be passed to either because the mother can see the baby's birth (Sunny et al, 2020).…”
Section: Theme 4: Variation Of Life Experiences Of Mothers During Prementioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study also showed for mothers undergoing operative delivery in patients with lumbar anesthesia that there are communications between patients and doctors in the surgery process. Communication is what makes mothers have life experience so that delivery by way of operative delivery is not scary, but it is a labor that can be passed to either because the mother can see the baby's birth (Sunny et al, 2020).…”
Section: Theme 4: Variation Of Life Experiences Of Mothers During Prementioning
confidence: 99%
“…The results of this study also show the triangulation of obstetricians and midwives, that the patient feeling satisfied and not satisfied is a relative thing and there are no specific indicators to measure satisfaction and dissatisfaction. It is emphasized that the team of healthcare providers, in carrying out its duties and obligations to patients, should be in accordance with SOP or the standard operating procedure that is in the hospital (Ashraf et al, 2019;Sunny et al, 2020). And every hospital is believed to have SOP and SOP in providing healthcare to mothers with GDM.…”
Section: Theme 8: Gaps and Desires Of People With Diabetes In Mothersmentioning
confidence: 99%
“… 14–19 Local Asian women with GDM reported ‘unpleasant OGTT experience’ as a barrier to postpartum T2DM screening. 18 …”
Section: Introductionmentioning
confidence: 99%
“…12 13 OGTT is inconvenient, time-consuming, labourintensive, and relatively costly, and often perceived as unpleasant. [14][15][16][17][18][19] Local Asian women with GDM reported 'unpleasant OGTT experience' as a barrier to postpartum T2DM screening. 18 The challenges of conducting OGTT have prompted the WHO to publish a set of conversion values for capillary and venous plasma glucose values.…”
mentioning
confidence: 99%
See 1 more Smart Citation